Pengembangan Media Audio Lirik Lagu Untuk Meningkatkan Motivasi Belajar Sejarah Siswa di Sekolah Menengah Atas - Nofriani Nofriani; Ofianto Ofianto (Jurnal Kronologi, 2020)
The study aims to develop Audio Media and Song Lyrics Collection Book as a medium of learning history that is feasible and practically used by teachers in history subjects in Senior High Schools. Type of research is research and development using the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The subjects of this research trial were 34 students of class X MIPA1 and 33 students of class X MIPA2 in SMAN 3 Padang Panjang. Data collection instruments used in this study was a questionnaire consisting of media validation test questionnaire, material validation test questionnaire, practicality test questionnaire by teachers and practicality test questionnaire by students. The research data were analyzed by qualitative and quantitative analysis techniques. The results showed that the validity of audio media and song lyric collection books based on the validation research of the material experts obtained an average of 3.59 and 3.50 media experts with very decent criteria. The practicality results obtained by the teacher averaged 3.36 with very practical criteria, while the practicality results obtained by students averaged 3.39 with very practical criteria. Thuse the audio media and song Lyric collection books developed are very feasible and practical to increase student’s motivation to learn history in high school.